A Rare Presentation of Hepatitis A Infection with Extrahepatic Manifestations - Geetika Bhatt; Varrinder S. Sandhu; Charlene K. Mitchell (Case Reports in Gastrointestinal Medicine)
Hepatitis A has a variety of associated extrahepatic manifestations that clinicians should be aware of for early diagnosis and treatment. We report a unique case of hepatitis A presenting with multiple extrahepatic manifestations not previously described in a single patient. A 34-year-old male presented with sudden onset of left sided facial pain, swelling, and skin rash, with diffuse body pains and muscle weakness, and was found to be positive for hepatitis A immunoglobulin M (IgM). He was initially started on antibiotics for concerns of bacterial parotitis but did not show any improvement. A punch biopsy of his mandibular rash and swelling was done which showed lymphohistiocytic infiltration with a few eosinophils. A trial of prednisone resulted in improvement of his symptoms. Clinicians should be aware to look for hepatitis A infection in a patient with atypical clinical picture causing a widespread systemic inflammatory response. Treatment with prednisone may result in resolution.